Conditional deletion of melanin-concentrating hormone receptor 1 from GABAergic neurons increases locomotor activity - Chee, Melissa J. (Mol Metab, 2019)
OBJECTIVE: Melanin-concentrating hormone (MCH) plays a key role in regulating energy balance. MCH acts via its receptor MCHR1, and MCHR1 deletion increases energy expenditure and locomotor activity, which is associated with a hyperdopaminergic state. Since MCHR1 expression is widespread, the neurons supporting the effects of MCH on energy expenditure are not clearly defined. There is a high density of MCHR1 neurons in the striatum, and these neurons are known to be GABAergic. We thus determined if MCH acts via this GABAergic neurocircuit to mediate energy balance. METHODS: We generated a Mchr1-flox mouse and crossed it with the Vgat-cre mouse to assess if MCHR1 deletion from GABAergic neurons expressing the vesicular GABA transporter (vGAT) in female Vgat-Mchr1-KO mice resulted in lower body weights or increased energy expenditure. Additionally, we determined if MCHR1-expressing neurons within the accumbens form part of the neural circuit underlying MCH-mediated energy balance by delivering an adeno-associated virus expressing Cre recombinase to the accumbens nucleus of Mchr1-flox mice. To evaluate if a dysregulated dopaminergic tone leads to their hyperactivity, we determined if the dopamine reuptake blocker GBR12909 prolonged the drug-induced locomotor activity in Vgat-Mchr1-KO mice. Furthermore, we also performed amperometry recordings to test whether MCHR1 deletion increases dopamine output within the accumbens and whether MCH can suppress dopamine release. RESULTS: Vgat-Mchr1-KO mice have lower body weight, increased energy expenditure, and increased locomotor activity. Similarly, restricting MCHR1 deletion to the accumbens nucleus also increased locomotor activity. Vgat-Mchr1-KO mice show increased and prolonged sensitivity to GBR12909-induced locomotor activity, and amperometry recordings revealed that GBR12909 elevated accumbens dopamine levels to twice that of controls, thus MCHR1 deletion may lead to a hyperdopaminergic state that mediates their observed hyperactivity. Consistent with the inhibitory effect of MCH, we found that MCH acutely suppresses dopamine release within the accumbens. CONCLUSIONS: As with established models of systemic MCH or MCHR1 deletion, we found that MCHR1 deletion from GABAergic neurons, specifically those within the accumbens nucleus, also led to increased locomotor activity. A hyperdopaminergic state underlies this increased locomotor activity, and is consistent with our finding that MCH signaling within the accumbens nucleus suppresses dopamine release. In effect, MCHR1 deletion may disinhibit dopamine release leading to the observed hyperactivity.